Temporomandibular disorders and relationship with socio-demographic and clinical variables in a University of the state of Rio de Janeiro - Barbosa, Renata Nogueira; Robles, Fábio Renato Pereira; Assaf, Andréa Videira; Silva, Marcelo Gomes Da; Mendes, Karine Laura Cortellazzi; Guimarães, Antônio Sérgio (Sociedade Brasileira para o Estudo da Dor, 2017)
ABSTRACTBACKGROUND AND OBJECTIVES: This study aimed at identifying the prevalence of suspected temporomandibular disorders in employees and students of a Brazilian university and at evaluating the influence of socio-demographic and clinical variables on this disorder.METHODS: This study had a non-probabilistic sample of 575 volunteers who were evaluated by a questionnaire proposed by the American Academy of Orofacial Pain.RESULTS: Suspected temporomandibular disorder was present in 60.87% of the population. By means of multiple logistic regression analysis, just clinical variables were associated to the presence of suspected temporomandibular disorder, such as: headache, neck pain or teethache (OR=47.60), stiff, tight or regularly tired jaws (OR=13.37), mouth opening difficulty (OR=13.55) and pain around the ears, temples or cheeks (OR=4.61).CONCLUSION: The questionnaire was effective as a pre-screening tool to identify symptoms, and results support the importance of clinical symptoms for the identification and follow up of patients with such disorders.

RESUMOJUSTIFICATIVA E OBJETIVOS: O objetivo deste estudo foi identificar a prevalência de suspeita de disfunção temporomandibular em funcionários e estudantes em uma universidade no Brasil e analisar a influência das variáveis sócio-demográficas e clínicas sobre essa disfunção.MÉTODOS: Este estudo teve uma amostra não probabilística compreendendo 575 voluntários que foram avaliadas por um questionário, proposto pela Academia Americana de Dor Orofacial.RESULTADOS: A suspeita de disfunção temporomandibular estava presente em 60,87% da população. Por meio da análise de regressão logística múltipla, apenas variáveis clínicas foram associadas com a presença de suspeita de disfunção temporomandibular, como: apresentar cefaleia, dores no pescoço ou nos dentes (OR=47,60), maxilares rígidos, apertados ou cansados com regularidade (OR=13,37), dificuldade na abertura da boca (OR=13,55) e dor ao redor das orelhas, têmporas ou bochecha (OR=4,61).CONCLUSÃO: O questionário foi eficaz como um instrumento de pré-triagem no levantamento dos sintomas; e os resultados suportam o ponto forte dos sintomas clínicos na identificação e acompanhamento de indivíduos com tais lesões.
Disfunções temporomandibulares e a relação com determinantes sócio-demográficos e clínicos em uma universidade do estado do Rio de Janeiro
Keywords: Epidemiology; Headache; Neck pain; Temporomandibular joint; Temporomandibular joint disorders; Articulação temporomandibular; Cefaleia; Cervicalgia; Epidemiologia; Transtornos da articulação temporomandibular